PEMBERDAYAAN KELOMPOK IBU-IBU RUMAH TANGGA MELALUI PENGEMBANGAN USAHA ANEKA KUE BERBAHAN TALAS DI KECAMATAN NGAGLIK KABUPATEN SLEMAN - Raharti, Rini; Kusdarjito, Cungki; Jatmiko, Bambang; Lestari, Puji; Qomariyah, Siti (Informasi Interaktif, 2019)
ABSTRACT The target of the program is that people who have not been economically productive but have a strong desire to become entrepreneurs, are a group of housewives with 10 members in the Dsn. Karanglo Sukoharjo Ngaglik Sleman. The aim of the program is to help empower housewives through the development of various taro-based cakes and help create peace and comfort. In general, the problems faced by partners are economic conditions that are still below average and productivity levels that are still low. To overcome this problem, the service team provided a solution in the form of building a business field tailored to the minimum skills of the community and local food-based partner areas. While the specific problem is that the majority of housewives are less able to take advantage of their free time in daily activities, do not have the effort to use taro around their home gardens as processed food, do not have the innovation of taro processing, do not have working capital to make business, do not have the ability to plan, record, and control a business, do not understand who the consumers will buy and do not know how to do the right marketing. The results of this activity are partners have received entrepreneurship training, the addition of production equipment, training and mentoring on how to make various cakes from taro, simple financial management training, and marketing management training.Keywords: taro, local food crops, empowerment, innovation, housewives